Seismic evidence for a thickened mantle transition zone beneath the Kamchatka subduction zoneKey points - Qinghui Cui; Yuanze Zhou; Yuan Gao; Ran Cui (Earthquake Science, 2025)
The structures of the mantle transition zone (MTZ) are of great significance for studying interactions of the subducted slab and deep mantle and related slab dynamics beneath subduction zones. Here by dense near-source SdP sampling from a large global dataset, we image topographies of transition zone discontinuities such as the 410-km and 660-km discontinuities (410 and 660) beneath the Kamchatka and conduct cross-section comparisons with the seismicity. Compared with the IASP91 model, the 410 exhibits apparent uplifts of 45−65 km with an average of 55 km in a horizontal width of ∼130 km, corresponding to low-temperature anomalies of 750−1083 K with an average of 916 K. In contrast, the 660 shows depressions of 15−37 km with an average of 25 km together with downward deflections in a width of ∼260 km, implying low-temperature anomalies of 161−397 K with an average of 268 K. Thus, we confirm a thickened MTZ with a thickness of 325−345 km around the cold descending Pacific slab. We suggest that topographic patterns of transition zone discontinuities imply a Pacific slab that has been significantly heated in the MTZ with broadened thermal effects on the 660. When considered along with other studies, we infer that the slab is possibly heated by hot mantle flows around the torn slab window extended to at least the MTZ range, thus inducing variations in thermal and rheological properties of the slab. Our seismic results can provide more insight into slab dynamics in the northwestern Pacific.